KARAKTERISTIK TEH HERBAL RAMBUT JAGUNG (Zea mays) DENGAN PERLAKUAN LAMA PELAYUAN DAN LAMA PENGERINGAN - Noviar Harun; Evy Rossi; Meiyanni Adawiyah (Jurnal Sagu, 2011)
Corn has not been used optimally, given that corn is the crop that can not be directlyconsumed. Withering and drying is a treatment process is usually done on herbal tea. This studyaims to look at long interaction length withering and drying of different herbal teas to the qualityof corn. This study was done at the Laboratory of Analysis and Processing of AgriculturalProducts Agricultural Faculty of Agricultural and Food Chemistry Laboratory of the Faculty ofFisheries University of Riau. The research was carried out experimentally using CompleteRandomized Design factorial pattern. The first factor is the length of the second factor is thewithering and drying time. Each of these factors consists of three stage with three replications inorder to obtain 27 combinations of samples. The results showed a long withering and drying timesignificantly affect the water content, crude fiber, and organoleptic assessment. Old differenceswithering and drying effect is not real time on ash content of corn produced. Coliform bacteriafound 3cfu/ml and do not exceed the specified SNI.Key words: corn, withering and drying, hair herbal tea corn